(untitled) (Global Journal of Medical Research, 2014)
Colorectal cancer is defined as the cancer of the large intestine or the rectum -thus attributing to some other names related to this cancer such as -bowel cancer or rectal cancer, depending on the site where the tumor has occurred. It mostly begins as a benign tumor with then turns into a carcinoma.Colon cancer and rectal cancer are related in terms of their genetics and thus are studied together as allied tumors. Although some other factors such as age and lifestyle are also concerned with the progression of this cancer, a minority group of people acquire it because of certain genetic predisposition, which is focused upon in this review. Initially it was thought only to occur because of certain mutations in a specific gene called adenomatous polyposis coli (APC) gene which are responsible for initiating the characteristic events which lead to the progression of this tumor.The cases affected by this pathway were called the LOH group. But further researches concluded that there is another different pathway which can lead to the occurrence of this tumor apart from the one briefly stated above.